2020
DOI: 10.18502/pbr.v6i(s1).4402
|View full text |Cite
|
Sign up to set email alerts
|

The Association Between Air Quality Parameters and COVID-19 in Turkey

Abstract: Background: Coronavirus disease 2019 (COVID-19) is an invisible enemy that has made people observe issues such as eating habits, personal hygiene, and environmental factors that may affect their immune systems. Objectives: Because air pollution can affect the immune system, it is necessary to examine the relationship between air quality parameters and COVID-19.  Methods: his study examines the correlation between air quality and COVID-19 considering 7 air pollutants: PM10, SO2, CO, NO2, NOx, NO, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…For instance, compared with the lockdown period, the eastern province of Saudi Arabia and its capital (Riyadh) recorded lower PM 10 levels, by 27–70% [6] and 91% [7] , respectively. Lower PM 10 concentrations were also recorded in nine provinces in Turkey [8] and Tehran, Iran [9] . Several other studies outside the region of the Arabian Peninsula have also reported a significant decline in PM 2.5 and PM 10 ; for instance, Almaty, Kazakhstan [10] , Milan, Italy [11] , Barcelona, Spain [12] , Delhi, India [13] , western Europe [14] , China [15] , and the 50 most polluted cities in the world [16] .…”
Section: Introductionmentioning
confidence: 92%
“…For instance, compared with the lockdown period, the eastern province of Saudi Arabia and its capital (Riyadh) recorded lower PM 10 levels, by 27–70% [6] and 91% [7] , respectively. Lower PM 10 concentrations were also recorded in nine provinces in Turkey [8] and Tehran, Iran [9] . Several other studies outside the region of the Arabian Peninsula have also reported a significant decline in PM 2.5 and PM 10 ; for instance, Almaty, Kazakhstan [10] , Milan, Italy [11] , Barcelona, Spain [12] , Delhi, India [13] , western Europe [14] , China [15] , and the 50 most polluted cities in the world [16] .…”
Section: Introductionmentioning
confidence: 92%
“…However, the simple approach adopted in this study, that does not allow variables such as wind speed and direction, temperature, relative humidity, mixing height, etc., and the effect of atmospheric chemistry or ongoing long-term trends to be taken into account, is a limitation. Şahin (2020) studied the correlation between COVID-19 cases and meteorological data in Turkey, reporting Spearman Rho coefficient ranges of [-0.32 – -0.48], [-0.30 – -0.40], [-0.32 – 0.02], and [-0.22 – 0.55], respectively for temperature, dew point, humidity, and wind speed ( Şahin, 2020 ), among which the highest correlation coefficient (0.55) belonged to wind speed (14 days ago).…”
Section: Resultsmentioning
confidence: 99%
“…Relationship between COVID-19 infection and short-term exposure to PM 2.5 , PM 10 , CO, NO 2 and O 3 were investigated in China ( Zhu et al., 2020a ), showing that daily counts of confirmed cases increased by 2.24 %, 1.76 %, 6.94 %, and 4.76 % with a 10 μg/m 3 increase in PM 2.5 , PM 10 , NO 2 , and O 3 , respectively. The correlation between seven air quality parameters (CO, NO, NO 2 , NO x , PM 10 , O 3 , and SO 2 ) and COVID-19 cases in Turkey was investigated using Spearman Rho and Pearson correlation analyses ( Şahin, 2020 ). It was reported that a significant correlation (r=0.617) between PM 10 and COVID-19 cases was observed.…”
Section: Resultsmentioning
confidence: 99%
“…Although there is no study that directly examines the relationship between the number of Covid-19 cases and air pollutants in Turkey, there are some studies on air pollution and Covid-19 pandemics for different provinces and regions of Turkey. Sahin [ 24 ] used correlation analysis to examine the difference between the number of Covid-19 cases and some air pollutant parameters for 9 big cities in Turkey and found a positive significant relationship between the SO 2 indicator and the number of Covid-19 cases. Dursun et al [ 25 ] investigated the effects of the measures taken during the Covid-19 pandemic (travel restriction, curfew, online education etc.)…”
Section: Introductionmentioning
confidence: 99%